Portofolio demi Sertifikasi Guru, Harapan atau Impian - Subijanto M.Ed (Badan Standar, Kurikulum, dan Asesmen Pendidikan, Kemendikbudristek, 2010)
A professional teacher is a yearned-for personnel in terms of creating qualified human resource for the Indonesian development. The government accomplished he yearning by the program of teacher certification that is aimed at specifying teacher appropriateness to become a teaching agent, increasing the quality of education success and teachers status, promote teachers professionalism and prosperity. In order to get a certificate the teacher has to possess academic qualification at least of bachelor or fourth diploma degree and has competency to realize the national education goal. In order to get the certificate the teacher has to pass the certification test as shown by various documents in the set of portfolio. Many people are skeptical towards the certification accomplishment because of the practices of corruption activities for the purpose of obtaining a piece of magical certificate that should be used to get the increase of teacher quality and income. This article is to spotlight numerous difficulties and barriers faced by the teachers in fulfilling the demands of portfolio so that the teacher certificate could become an aspiration that would be accomplished or on the contrary it would be nothing other than a dream because of the impossibility to fulfill the certification demands.Â ABSTRAKGuru profesional menjadi dambaan bangsa karena akan menjadi pencipta sumber daya manusia berkualitas demi tersedianya tenaga pembangun berkualitas bagi bangsa Indonesia. Pemerintah mewujudkan dambaan itu melalui program sertifikasi guru yang bertujuan untuk menentukan kelayakan guru sebagai agen pembelajaran, meningkatkan mutu hasil pendidikan dan martabat guru, serta meningkatkan profesionalitas guru dan kesejahteraannya. Untuk mendapatkan sertifikasi itu guru harus memiliki kualifikasi akademik minimum sarjana atau diploma empat dan kompetensi mewujudkan tujuan pendidikan nasional. Demi mendapatkan sertifikasi itu guru harus lulus dalam uji sertifikasi yang dibuktikan dengan berbagai dokumen dalam berkas portofolio. Banyak pihak bersikap skeptis terhadap pelaksanaan sertifikasi karena kuatir terjadinya praktik-praktik KKN demi selembar sertifikat sakti menuju peningkatan kualitas dan pendapatan guru. Tulisan ini menyorotkan berbagai kesulitan dan kendala yang dihadapi guru dalam memenuhi tuntutan portofolio sehingga sertifikasi guru dapat menjadi suatu harapan yang bakal terpenuhi atau sebaliknya merupakan impian semata karena kemustahilan memenuhi tuntutan sertifikasi.Â